“ME – YOU”: SOCIAL PEDAGOGUE’S HELP FOR SOCIAL RISK CHILDREN IN TERMS OF INTERRELATIONSHIP - Ratkeviciene, Milda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Social pedagogue’s help for social risk children is a relevant part of education and of our society as well in Lithuania and in the world in general. The purpose of article is to describe social pedagogue’s help for social risk children through interrelationship perspective. Every relationship between social pedagogue and social risk child has different story. But the results presented in this article show all interrelationships between these two persons have the same idea – the respectful trust or trust-based respect is necessary. Only such relationships can create conditions for the provision of professional and effective help for social risk children both in short-term and long-term perspective. Interrelationship “me – you” between school social pedagogue and social risk children is looked through the ideas of A. Lingis and M. Buber. The research is based on the phenomenological narrative perspective.